On the Economics of Compliance with the Minimum Wage Law - Chang, Yang-Ming; Ehrlich, Isaac (Journal of Political Economy, 1985)
This paper reexamines the issues of compliance with and enforcement of the minimum wage law recently addressed in this Journal by Ashenfelter and Smith and by Grenier. Pursuing a more rigorous methodology we are able to add new general conclusions, and correct and reconcile some previous conflicting conclusions concerning the role of the disparity between the minimum and free market wages, the level and elasticity of labor demand, and the magnitude of deterring monetary sanctions on the noncompliance decision. Our formulation also addresses the law evasion (reduced wages) as well as the law avoidance (modified employment) aspects of the noncompliance decision, which previous formulations have ignored.